Homeric enunciation and the practice of invocation to the Muse (Circe de clásicos y modernos, 2018)
Homeric invocation to the Muse var-ies in nature and in function. The bard solicits to the Muse sometimes the gift of chant and poetic art in general in the initial invocation, some other times, precise information about facts in the enumerative invocation, and some others the capacities of memory and of arrangement of the facts in the narrative invocation. In another level, the function of the Muses is to rejoice the gods with their chants whereas they address to the poet in a rapport of direct communication in order to grant him the means to develop a poetic discourse at the same time personal and original.
Keywords: enunciation; Homer; Muse; invocation; discourse